Implementation of the CTL Model as a Strategy to Increase Interest in Learning Mathematics - Siswanto, Deny Hadi; Alghiffari, Eka Kevin; Pujiastuti, Nur Ika (Indonesian Journal of Educational Science and Technology, 2024)
This research aims to increase interest in learning mathematics in class XI students at SMA Muhammadiyah Mlati in the even semester of the 2023/2024 academic year by implementing the Contextual Teaching and Learning (CTL) model. This research uses a classroom action research method with a qualitative approach, involving 30 students as research subjects. Data collection methods include observation, questionnaires, and tests. Observations were made to understand students' learning interests, while questionnaires and tests were used to assess mastery of the Matrix material and the effectiveness of learning using the CTL model. Data analysis includes observation analysis, questionnaire analysis, and learning evaluation. This research shows the results of an increase after implementing the CTL model in Matrix learning in class XI MIPA. By implementing the CTL model, students' interest in learning increased, as evidenced by the results of observations which showed an increase in scores from the initial stage, cycle I, to cycle II, with a score reaching 3.62 which was categorized as very high. Students' ability to understand Matrix material also increased to reach an average score of 78.27 in cycle II.